Relationship between BMI and emotion-handling capacity in an adult Finnish population: the Northern Finland Birth Cohort 1966 - Ramzi, NH; Yiorkas, A; Sebert, S; Keinanen-Kiukaanniemi, S; Ala-Mursulu, L; Jokelainen, J; Veijola, J; Avinen, J; Miettunen, J; Dovey, T; Jarvelin, M-R; Blakemore, A (Public Library of Science, 2018)
Background: Alexithymia, a difficulty in identifying and expressing emotions, has been associated with obesity and eating disorders in small-scale cross-sectional studies. Here, we assess the relationship between baseline body mass index (BMI) and alexithymia in a large cohort of free-living Finnish adults over a 15-year period. Methods: Participants were drawn from the Northern Finnish Birth Cohort 1966 (NFBC1966). The 20-Item Toronto Alexithymia Scale (TAS-20) was used as a measure of alexithymia and was completed at the age of 31 years (31y: n=4841), 46 years (46y: n=5404). BMI was recorded at both time points. Where data at both time points were available (n=3274), the relationship between changes in BMI and TAS-20 over this time period was also investigated. Results: BMI was significantly and positively associated with TAS-20 score (p<0.0001, both ages), both at 31 years and at 46 years. The association remained statistically significant after adjustment for potential confounders (sex, marital status and several socio-economic indicators). In individuals who experienced BMI greatest change in both directions over the 15-year period, there was a modest mean increase in TAS-20 score. Conclusions: Our data revealed that TAS-20 score increased and co-varied with body mass status. We suggest that future clinical research should consider the role of alexithymia in obesity. Further investigation of this relationship is warranted to ensure that the needs of obese subjects with undiagnosed alexithymia are considered in the design of weight management programmes.